2021
DOI: 10.1186/s40168-021-01148-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium phosphate strongly impacts gut microbiome changes elicited by inulin and galacto-oligosaccharides consumption

Abstract: Background Fructo-oligosaccharides (FOS), inulin, and galacto-oligosaccharides (GOS) are widely recognized prebiotics that profoundly affect the intestinal microbiota, including stimulation of bifidobacteria and lactobacilli, and are reported to elicit several health benefits. The combination of dietary FOS and inulin with calcium phosphate was reported to stimulate commensal Lactobacillus populations and protect the host against pathogenic Enterobacteriaceae, but little is known about the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 91 publications
2
32
0
3
Order By: Relevance
“…Several studies have revealed the potential ability of Erysipelotrichaceae, Bifidobacterium, Faecalibaculum, Bacteroides, and Romboutsia to produce SCFAs [51,52]. SCFAs, composed of acetic acid, propionic acid, butyric acid, etc., have been identified as cardinal examples of beneficial metabolites [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the potential ability of Erysipelotrichaceae, Bifidobacterium, Faecalibaculum, Bacteroides, and Romboutsia to produce SCFAs [51,52]. SCFAs, composed of acetic acid, propionic acid, butyric acid, etc., have been identified as cardinal examples of beneficial metabolites [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Muribaculaceae plays multiple functions in degrading complex carbohydrates (39). Similar to Bifidobacterium and Lactobacillus , Faecalibaculum can produce lactic acid and short-chain fatty acids and has anti-colon cancer effects (40). It protects the stability of the intestinal environment and prevents pathogens from colonizing in the intestinal epithelium, which has health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics are indigestible food ingredients that improve the gut microbiota structure by providing carbon sources, making metabolic substrates available for the gut microbiota to utilize, and adjusting the gut microenvironment, such as in terms of pH value, gastrointestinal absorption, and enzyme hydrolysis ( 173 , 174 ). Fructo-oligosaccharide (FOS) is a well-studied effective prebiotic consisting of one glucose and one fructose, and it has shown multiple beneficial effects in several animal models including the following: (a) resisting bacterial infection such as that of enterotoxigenic E. coli ( 176 ), (b) promoting the colonization of probiotics like Bifidobacterium and Lactobacillus ( 177 180 ), (c) increasing the production of SCFAs by the use of these probiotics ( 180 ), and (d) downregulating the pro-inflammatory cytokine expression and protecting the mucosal barrier ( 181 ). Besides FOS, inulin, galacto-oligosaccharides, and some foods containing indigestible β-glucans such as termites, a kind of Chinese traditional medicine, also have a similar effect ( 174 ).…”
Section: Prospects Of Interventions Targeting Glucose Metabolism Glyc...mentioning
confidence: 99%